Pandangan Teologi Terhadap LGBT (Lesbian, Gay, Biseksual Dan Transgender) - Yulian Anouw; Chelsya Chintya Pattiata (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The background of this research problem is to find out (a) what factors influence the occurrence of LGBT (Lesbian, Gay, Bisexual and Transgender); (b) the role of the family and church in dealing with LGBT (Lesbian, Gay, Bisexual and Transgender); (c) Christian theological views on LGBT. The research was conducted using qualitative research methods, namely interviews and internet sites. Data results obtained through interviews. The research results show: LGBT is a sexual deviation, which cannot be denied, Christians also fall into it. LGBT behavior is an abominable act in the eyes of God. This creates negative things in people's lives and health. Parents play a very important role in educating children, providing correct sex education that is in accordance with God's Word. This LGBT group has the right to repentance in Jesus. Because that is why Jesus came into the world to save humans from sin. The church also has a very important role in providing assistance to LGBT groups.